Forest-based solutions for reconciling natural hazard reduction with biodiversity benefits - F. Rey; S. Dupire; F. Berger (Nature-Based Solutions, 2024)
Nature-based solutions (NbS) offer ways to preserve, restore and manage ecosystems to meet today's societal challenges by combining benefits for society and biodiversity. They incorporate natural features and processes into projects to ensure their sustainable development while investing in the integrity of ecosystems. “Forest-based solutions” (FbS) can be identified as NbS forests that provide both human well-being and biodiversity benefits. In this paper, we intend to consider FbS as solutions that help reconcile natural hazard control with biodiversity benefits, and especially highlight the practices and research needs in this field. FbS in this article correspond specifically to forests used or managed for mitigating natural hazards linked to gravity (rockfalls and avalanches) or to water (floods and drought), while preserving, restoring or managing biodiversity. Firstly, we review the definition and development of FbS applied to natural hazard reduction, while stressing issues concerning the design, implementation, and monitoring of these kinds of actions. Secondly, we point out the need to combine natural hazard control with restoration, preservation and management of ecosystems, by posing novel practice and research questions.